Model TV. - Cardin, Marlene McGinnis; Charney, Nicolas H. (Videofashion, 2007)
"We chat with Daria Werbowy, the classic Canadian beauty who has been a mainstay of the modeling world for the past four years. Meet fifteen-year-old newcomer Tanya Dziahileva, and fresh face Coco Rocha who is pleased to have a first name that is quite familiar to the fashion world. Veteran Swedish model Caroline Winberg offers advice to young women aspiring to break into the profession, and we hit the streets with David Jinsin to hear how he is taking the New York fashion world by storm. In Milan, Flavia de Oliveira has some kind words to say about her predecessor Gisele Bundchen, and in Miami, swimsuit model and Sports Illustrated regular Marisa Miller takes a break from her busy schedule. Finally, we catch up with Hilary Rhoda, the U.S. model who is causing industry insiders to once again use "American" and "Supermodel" in the same sentence."--Publisher website.